'Dieu et le sexe. Le pur et l'impur': Concilier l'Islam et l'homosexualité chez Rachid O. et Abdellah Taïa. (1st December 2013) - Ncube, Gibson
Although homosexuality is palpably present in Arab-Muslim societies of the Maghreb, there is nonetheless intolerance of their open discussion. Even on a purely discursive level, taboo remains an insurmountable hurdle. The present study attempts to contribute to growing debate and interest in various aspects and potential common points between literary production and 'marginal' sexuality in Francophone North Africa. This article problematizes homosexuality in Arab-Muslim societies before examining its depiction in the autofictional novels of two openly gay Moroccan writers: Rachid O. and Abdellah Taïa. Of particular interest in this literary analysis is the manner in which the protagonists of the two novelists grapple in reconciling their (homo)sexuality and their religious beliefs. This article concludes by scrutinizing the transgressiveness of these pioneering contemporary novels in their candid and open representation homosexuality.Bien que l'homosexualité soit manifestement présente dans les sociétés arabo-musulmanes du Maghreb, sa discussion ouverte demeure intolérable. Même sur un plan purement discursif, le tabou reste un obstacle insurmontable. La présente étude vise à contribuer au débat et à l'intérêt croissants par rapport aux divers aspects et aux points communs potentiels entre la production littéraire et la sexualité 'marginale' dans les milieux francophones de l'Afrique du Nord. Cet article problématise initialement l'homosexualité dans les sociétés arabo-musulmanes avant d'examiner sa représentation dans les romans autofictionnels de deux écrivains marocains qui sont ouvertement gay: Rachid O. et Abdellah Taïa. L'intérêt particulier de cette analyse littéraire sera la manière dont les protagonistes des deux romanciers se négocient la difficulté de concilier leur (homo)sexualité et leurs croyances religieuses. Cet article examine, en guise de conclusion, la nature transgressive de ces romans contemporains pionniers dans leur représentation franche et ouverte de l'homosexualité.